Bank Loans and Stock Prices: An Empirical Evidence - Bakri Abdul Karim; Lim Siew Lih; Zulkefly Abdul Karim (Aceh International Journal of Social Science, 2012)
Abstract - This study re-examines the interaction between bank loans and stock prices in Malaysia. We use Granger non-causality test proposed by Toda and Yamamoto (1995) in both bivariate and multivariate frameworks and both monthly and quarterly data in examining the relationship between the two variables. Unlike previous studies, we find that there is strong evidence of no causality running between stock prices and bank loans in all models and samples. This finding revealed that stock prices and bank loans are independent. The predictability of stock prices cannot be enhanced considerably through utilizing information on the bank loans.